2011
DOI: 10.5604/15093492.971039
|View full text |Cite
|
Sign up to set email alerts
|

Fingertip injuries in children treated in Department of Pediatric Surgery and Oncology in the years 2008-2010.

Abstract: Fingertip injuries are among the most common injuries in children and preservation of the hand's motor abilities depends on thorough surgical care. Most children with fingertip injuries are treated in Emergency Units and only 10% of patients need surgery under general anaesthesia after hospital admission. A number of surgical techniques can be used in the management of fingertip injuries in children. These techniques represent adaptations of methods used in adults. A model for the evaluation of severity and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…1 Younger children are curious and more apt to explore their environment using their hands without realizing the dangers involved. Our findings also support the outcomes of several other studies where the average pediatric fingertip injury patient is 5 years of age 2,5,8,9,12 ; our study had a higher average, 8 years, possibly because of our larger sample size. Fingertip injuries occur relatively equally among males and females, although our results support previous studies that show these injuries to be more prevalent among males.…”
Section: Demographicssupporting
confidence: 91%
See 2 more Smart Citations
“…1 Younger children are curious and more apt to explore their environment using their hands without realizing the dangers involved. Our findings also support the outcomes of several other studies where the average pediatric fingertip injury patient is 5 years of age 2,5,8,9,12 ; our study had a higher average, 8 years, possibly because of our larger sample size. Fingertip injuries occur relatively equally among males and females, although our results support previous studies that show these injuries to be more prevalent among males.…”
Section: Demographicssupporting
confidence: 91%
“…Fingertip injuries occur relatively equally among males and females, although our results support previous studies that show these injuries to be more prevalent among males. 1,2,5,9 Like numerous other studies, 2,5,8,9,12 we found that more fingertip injuries occurred in the right hand (n = 939, 52%), than the left hand (n = 847, 47%). Our findings support the results of other studies that show the middle finger to be the most commonly injured digit.…”
Section: Demographicssupporting
confidence: 79%
See 1 more Smart Citation
“…Young children are among the most frequently affected group (Al-Qadhi et al., 2011; Kubus et al., 2011; Yorlets et al., 2017). The age distribution graph in Figure 1 demonstrates a higher proportion of younger children undergoing surgery compared with adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that fingertip injuries most frequently result from a crush injury, often from the hinge side of a door (Al-Anazi, 2013; Al-Qadhi et al., 2011; Kubus et al., 2011). Approximately 50% of nail bed injuries presenting to hospital are associated with distal phalangeal fractures (Satku et al., 2015), and the resulting consequences can be serious.…”
Section: Introductionmentioning
confidence: 99%